2021
DOI: 10.1109/access.2021.3085949
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Combinatory Effect of Uniaxial Electrical and Magnetic Anisotropy on the Input Impedance and Mutual Coupling of a Printed Dipole Antenna

Abstract: The main objective of this work is to investigate the combinatory effects of both uniaxial magnetic and electrical anisotropies on the input impedance, resonant length and the mutual coupling between two dipoles printed on an anisotropic grounded substrate. Three different configurations: broadside, collinear and echelon are considered for the coupling investigation. The study is based on the numerical solution of the integral equation using the method of moments through the mathematical derivation of the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Particularly, the effect of the complex elements on the input impedance, resonant length and mutual coupling of two printed dipoles and hence, antenna performance according to the collinear, echelon and broadside configurations. The study extends our previous our works 10 , 22 , 23 , where only anisotropic and bi-isotropic medium cases were treated. It is based on a spectral theoretical formulation and a numerical solution technique using the moments method in the spectral domain; a method that is well known in the analysis of microwave planar structures 7 , 27 .…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Particularly, the effect of the complex elements on the input impedance, resonant length and mutual coupling of two printed dipoles and hence, antenna performance according to the collinear, echelon and broadside configurations. The study extends our previous our works 10 , 22 , 23 , where only anisotropic and bi-isotropic medium cases were treated. It is based on a spectral theoretical formulation and a numerical solution technique using the moments method in the spectral domain; a method that is well known in the analysis of microwave planar structures 7 , 27 .…”
Section: Introductionsupporting
confidence: 79%
“…It is shown that surface waves increase the mutual coupling in a fixed linear arrangement of the printed dipoles and contribute to the cross-coupling. This also shows that the complex media present a great potential in the design of innovative microwave components 22 , 23 .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…When the temperature is between T 1 and T 2 , the antenna switches to a dipole antenna configuration ( Figure 2 b), and the impedance changes to 73 + 9 j Ω. Although a standard dipole is better at radiating geometrically, the improperly matched input impedance of the antenna will cause an overall weaker radiation [ 45 , 46 ]. As a result, the minimal magnitude of the return loss S 11 around 950 MHz decreases from 23 dB to 16 dB.…”
Section: Principle Of Shmoamentioning
confidence: 99%
“…Some miniaturization methods useful in electronic systems have been reported recently. [1][2][3][4][5][6][7][8][9][10][11][12][13] In that context, system mathematical modeling and subsequent thermal management optimization are highly desirable to deal with system energy efficiency demand, costs reduction, and environmental impact minimization. In that sense, the requirement for system response direct assessment or computer simulation of a multitude of viable configurations for different operating parameters sets needs to be tackled by fast and sufficiently accurate models.…”
Section: Introductionmentioning
confidence: 99%